2021
DOI: 10.1021/acs.nanolett.1c02422
|View full text |Cite
|
Sign up to set email alerts
|

Charged Bosons Made of Fermions in Bilayer Structures with Strong Metallic Screening

Abstract: Two-dimensional monolayer structures of transition metal dichalogenides (TMDs) have been shown to allow many higher-order excitonic bound states, including trions (charged excitons), biexcitons (excitonic molecules), and charged biexcitons. We report here experimental evidence and the theoretical basis for a new bound excitonic complex, consisting two free carriers bound to an exciton in a bilayer structure. Our experimental measurements on structures made using two different materials show a new spectral line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2

Relationship

7
2

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…The Drude plasma frequency, ω pD , as extracted from the ellipsometry fitting, red-shifts in thinner films going from 7.47 eV for the 10 nm thick film to 6.92 eV for the 1 nm thick film (Figure a). To understand the observed dependence of the plasma frequency on the thickness, we use the confinement-induced nonlocal Drude dielectric response model recently developed for plasmonic TDMs with finite thickness. ,, Our nonlocal dielectric response model is based on the KR pairwise electron interaction potential , to describe charged elementary excitations and their electrostatic interactions in vertically confined TDMs. ,, The KR potential accounts for the electrostatic interaction between a pair of charge carriers confined in a layer of thickness d , which is mostly due to the dielectric surroundings rather than by the material of the layer itself. When d is less than the typical in-plane distance between the carriers, the electrostatic interaction potential of the charge carriers inside the layer is no longer of the Coulomb form.…”
mentioning
confidence: 99%
“…The Drude plasma frequency, ω pD , as extracted from the ellipsometry fitting, red-shifts in thinner films going from 7.47 eV for the 10 nm thick film to 6.92 eV for the 1 nm thick film (Figure a). To understand the observed dependence of the plasma frequency on the thickness, we use the confinement-induced nonlocal Drude dielectric response model recently developed for plasmonic TDMs with finite thickness. ,, Our nonlocal dielectric response model is based on the KR pairwise electron interaction potential , to describe charged elementary excitations and their electrostatic interactions in vertically confined TDMs. ,, The KR potential accounts for the electrostatic interaction between a pair of charge carriers confined in a layer of thickness d , which is mostly due to the dielectric surroundings rather than by the material of the layer itself. When d is less than the typical in-plane distance between the carriers, the electrostatic interaction potential of the charge carriers inside the layer is no longer of the Coulomb form.…”
mentioning
confidence: 99%
“…We expect the measured distance dependence of dielectric screening to be valid for various kinds of two-dimensional bilayer structures. Such systems have recently become of interest in several contexts, such as for the investigation of interlayer excitons 4 , doubly charged excitons 42 , excitonic Bose-Einstein condensation 43 , correlation effects 44 as well as for the investigation of light-matter interactions in TMD superstructures 45 . We have furthermore shown that electrostatically varying the charge carrier density of graphene in the vicinity of a TMD allows for a continuous and significant change in Coulomb interactions even at room temperature.…”
Section: Discussionmentioning
confidence: 99%
“…With thickness of only a few atomic layers, ultrathin TD films of metals, doped semiconductors, or polar materials can support plasmon-, exciton-, magnon-, and phonon-polariton eigenmodes. [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] Plasmonic TD materials (ultrathin metallic films) offer controlled light confinement, large tailorability and dynamic tunability of their optical properties due to their thickness-dependent localized surface plasmon (SP) modes, [14][15][16][17][18][19][20][21] which are distinctly different from those of conventional thin films commonly described by either purely 2D or by 3D material properties with boundary conditions imposed on their top and bottom interfaces. [33][34][35][36][37][38][39][40][41] In such systems, the vertical quantum confinement enables a variety of new quantum phenomena, including the thickness-controlled plasma frequency red shift, 2,11 the SP mode degeneracy lifting, 14,18 a series of magneto-optical effects, 13 and even atomic transitions that are normally forbidden, 1,...…”
Section: Introductionmentioning
confidence: 99%